Desain Prototype Smart Building Menggunakan Internet of Things dengan Protokol MQTT - Evta Indra; Mohammad Irfan Fahmi; Daniel Ryan Hamonangan Sitompul; Stiven Hamonangan Sinurat; Andreas Situmorang; Ruben Ruben; Dennis Jusuf Ziegel (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2022)
Energy saving is the most wanted thing to prevent overspending in carrying out daily activities in the building. One form of energy savings is implementing Smart Building technology to control Air conditioners (AC) dan lamps according to its need. Methods used in this research were started with the Architectural Design of the devices, Managing of the devices, and their Decommission. The result carried in this research is that the prototype made was running well on low-scale implementation. Buttons in the website functioned well, even though there are still many problems when implementing the project on a huge scale because this research still uses a freeware-based MQTT broker.